Fish Assemblages in Murum Hydroelectric Reservoir and Plieran River, Belaga, Sarawak - Kirollina, Kisun. (Universiti Malaysia Sarawak, (UNIMAS), 2015)
Fish survey and selected water quality sampling were conducted on 7th to 9th of July 2014 and 25th to 27th February 2015 at Murum Hydroelectric Reservoir and Plieran River. Currently, there is not much information available on the fish composition in Belaga area, especially at Murum Dam and Plieran River. Therefore, this study was conducted to determine the fish assemblages and condition of water quality at Murum Hydroelectric Reservoir and Plieran River, Belaga. Data collected could be used as baseline data and also for future monitoring and management purposes. A total of 670 individuals of fishes were caught in July 2014. Based on the identification, a total of 13 species was found from 4 families. The highest number was Barbodes binotatus with 46.72% and followed by Oreochromis niloticus which was 25.97%. The lowest was Osteochilus pleurotaenia with 0.30%. In February 2015, a total of 321 individuals of fishes were caught comprising 14 species and 4 families. The highest number caught was Hampala bimaculata with 31.15%, followed by Barbonymus schwanenfeldii with 18.69% and Oreochromis niloticus with 17.45%. The lowest is shared by Luciosoma setigerum and Macrognathus maculatus, each with 0.31%. Results shows that in July 2014, the depth ranged from 6.4 m to 11 m whereas in February 2015, depth ranged from 8.4 m to 19.2 m. Temperature in July 2014 ranged from 24.9 °C to 31.6 °C and 28.3 °C to 29.86 °C in February 2015. DO range from 5.2 mg/L to 6.6 mg/L and 4.13 mg/L to 7.5 mg/L in July 2014 and February 2015, respectively. pH ranged from 6.51 to 7.73 in July 2014 whereas in February 2015, it was from 6.07 to 7.7. For chlorophyll a, the highest was recorded in July 2014 (3.0719 µg/L) and the lowest was in February 2015 with 0.1294 µg/L.